Radial Artery Catheterization for Neuroendovascular Procedures: Clinical Outcomes and Patient Satisfaction Measures. Issue 9 (September 2019) - Khanna, Omaditya; Sweid, Ahmad; Mouchtouris, Nikolaos; Shivashankar, Kavya; Xu, Vivan; Velagapudi, Lohit; Stricsek, Geoffrey; Amllay, Abdelaziz; Texakalidis, Pavlos; Gooch, M. Reid; Tjoumakaris, Stavropoula; Rosenwasser, Robert H.; et al.
Abstract : Background and Purpose—: Radial artery catheterization is an alternate route of access that has started to gain more widespread use for neuroendovascular procedures, and there have been few studies that describe its safety and efficacy. We present our institution's experience in performing neuroendovascular interventions via a transradial approach, with excellent clinical outcomes and patient satisfaction measures. Methods—: We conducted a retrospective analysis and identified 223 patients who underwent 233 consecutive neuroendovascular interventions via radial artery access at our institution. The incidence of perioperative and postprocedural complications was investigated. We identified a subset of 98 patients who have undergone both transradial and transfemoral cerebral angiograms and compared clinical outcomes and patient satisfaction measures between the 2 groups. Results—: The overall incidence of complications was low across all procedures performed via transradial access. Peri-procedurally, only 2 patients had symptomatic radial artery spasm, and there were no instances of iatrogenic complications (vessel dissection, stroke, and hemorrhage). In 10 cases (4.3%), the intended procedure could not be completed via a transradial approach, and, thus, femoral artery access had to be pursued instead. Ten patients complained of minor postprocedural complications, although none required therapeutic intervention. The mean procedure time was shorter for diagnostic angiograms performed via transradial versus transfemoral access (18.8±15.8 versus 39.5±31.1 minutes; P =0.025). Patients overall reported shorter recovery times with transradial access, and the majority of patients (94%) would elect to have subsequent procedures performed via this route. Conclusions—: Radial artery catheterization is a safe and durable alternative to perform a wide range of neuroendovascular procedures, with a low rate of complications. On the whole, patients prefer transradial compared with transfemoral access. Abstract : Supplemental Digital Content is available in the text.